Management Education – The Semitic and Indo-European Languages: Arabic, Russian, Spanish languages. - Allegra, Stefania (International Journal of Scientific Research and Management (IJSRM), 2020)
The ability to work in more tasks in every field in life, is a hard goal to achieve. I can affirm with proof that you need to train constantly for it. It means that you have to train the mind and action through the same direction. I’ve been trained myself in this task with my own personal life experiences. Since I was twenty I’ve held many important and hard tasks that have changed my mind results.It’s the same in the field of learning, studying and teaching foreign languages. If you don’t train almost every day your memorization, it’s quite impossible to learn a foreign language. A professional professor in foreign languages is normally used to teach one, two languages or sometimes more, and it’s difficult in any case.According to my experience I got the special training to teach many languages, I mean at the same time, to switch from one language to another. So it happens that I teach more languages in the same day and even in the same hour, without any difficulty. It’s possible only because my mind is always well trained.For example, when you change languages, you must remember all skills, from all languages. So when I teach English, German, French, Russian, Arabic, Italian, etc.. It’s not easy to train the mind in this way, but you can succeed if you do the right training.It’s important to be conscious about the power of the mind, when we want to learn a foreign language. It’s not easy but you must focus on training hard to get true results.The mistake is to think to learn a language without passion just as chore, this way you will never learn it; passion is the first step in helping the memorization. Then you will find the next step to follow the training of memorization.